Aplikasi Rekomendasi Pengemudi Perusahaan Jasa Travel Bismar Trans dengan Metode Simple Additive Weighting - Benediktus Marcelino Pratama; Kartika Gunadi; Alexander Setiawan (Jurnal Infra, 2020)
Bismar Trans Travel Services Company is one of the engaged in transportation. During this time there are internal problems, one of which is the selection of the driver. So there needs to be a solution.This research was conducted to find the best driver. Travel Services Company Bismar Trans as a job provider uses the driver's recommendation application with the Simple Additive Weighting method with the PHP Programming Language, and the MySQL database.The results showed that the system calculation results were in accordance with the company's weight and criteria, the application could provide appropriate recommendations according to the company's needs and from the results of the questionnaire, the program had a good appearance, produced the right results, and had benefits.